Peran Balai Latihan Kerja Dalam Menanggulangi Pengangguran Di Kabupaten Pidie - Zulfikar, Zulfikar; Rozaili, Rozaili; Zulkifli, Zulkifli (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This study aims to analyze the role of Job Training Centers (BLK) in reducing unemployment in Pidie Regency. Using a descriptive method with a qualitative approach, the research incorporates observations and interviews with BLK trainees and instructors. The findings reveal that BLK has successfully contributed to reducing unemployment by training 5,220 participants over the past five years. Of these, 55% secured jobs, 35% are still seeking employment, and 10% were unsuccessful. Competency-based training emphasizing practice (75%) over theory (25%) positively impacted participants' skills and confidence. However, limited facilities and capacity hinder the absorption of prospective trainees. This study recommends improving training facilities, developing mobile training programs, and collaborating with other institutions to expand training outreach. BLK is expected to continue serving as a solution for enhancing employability and reducing unemployment in Pidie Regency.